Larval habitats of the Anopheles farauti and Anopheles lungae complexes in the Solomon Islands. (December 2016) - Russell, Tanya; Burkot, Thomas; Bugoro, Hugo; Apairamo, Allan; Beebe, Nigel; Chow, Weng; Cooper, Robert; Collins, Frank; Lobo, Neil
Abstract Background There is an urgent need for vector control tools to supplement long-lasting insecticidal nets (LLINs) and indoor residual spraying; particularly in the Solomon Islands where the primary vector, Anopheles farauti, is highly anthropophagic and feeds mainly outdoors and early in the evening. Currently, the only supplementary tool recommended by the World Health Organization is larval source management (LSM). The feasibility and potential effectiveness of LSM requires information on the distribution of anophelines, the productivity of larval habitats and the potential impacts of larval control on adult fitness. Methods The distribution of anophelines in Central and Western Provinces in the Solomon Islands was mapped from cross-sectional larval habitat surveys. The composition and micro-distribution of larval instars within a large permanent river-mouth lagoon was examined with a longitudinal survey. Density-dependent regulation ofAn. farauti larvae was investigated by longitudinally following the development and survival of different densities of first instars in floating cages in a river-mouth lagoon. Results Five anopheline species were molecularly identified from a range of fresh and brackish water habitats:An. farauti s.s., An. hinesorum, An. lungae, An. nataliae andAn. solomonis . The most common habitats used by the primary malaria vector, An. farauti, were coastal lagoons and swamps. In the detailed study of lagoon micro-productivity, An. farauti was non-uniformly distributed with highest densities found at collections sites most proximal and distal to the mouth of the lagoon. The survival ofAn. farauti larvae was more than twofold lower when larvae were held at the highest experimental density (1 larva per 3.8 cm2 ) when compared with the lowest density (1 larva per 38 cm2 ). Conclusions The only documented major malaria vector collected in larval surveys in both Central and Western Provinces wasAn. farauti . Lagoons and swamps, the most common, largest and (potentially) most productive larval sites of this malaria vector, were "few, fixed and findable" and theoretically, therefore, amenable to successful LSM. However, the immense scale and complexity of these ecosystems in whichAn. farauti larvae are found raises questions regarding the ability to effectively control the larvae, as incomplete larviciding could trigger density dependent effects resulting in increased larval survivorship. While LSM has the potential to significantly contribute to malaria control of this early and outdoor biting vector, more information on the distribution of larvae within these extensive habitats is required to maximize the effectiveness of LSM.